A ORGANIZAÇÃO DO TERRITÓRIO A PARTIR DO PARADIGMA DA AGROECOLOGIA NA COMUNIDADE EMILIANO ZAPATA – PONTA GROSSA – PR. - Engelmann, Sandra Andrea (2011)
This study aimed to analyze the Agroecology as a possible choice of organization in the conquered territories (camps and settlements) by the Movement of Landless Rural Workers - MST in the State of Paraná. Was established as a field review the Pre-Settlement Emiliano Zapata, in the city of Ponta Grossa. What I focus was to understand how they are being discussed and implemented the assumptions of Agroecology in the peasant world. The peasants were seen as political subjects that have logical resistance and reproduction, in a dialectical relationship between commodity exchange and practice of reciprocity, as main features. Agroecology brings his understanding of both broad concepts, but also more restrictive notions. Discussions by step into scientism, some scholars consider it a science, others as a focus, but also to those who set a methodological tool or as a model of agricultural production. This multiplicity of understandings should not be understood in isolation, but so interconnected, from a holistic approach and a systemic approach. The design of Agroecology proposes a break with the rural development model based on the latifundia, monoculture, in agribusiness, which has become the hegemonic control of power in the Brazilian countryside. Thus, conceive it suggests a direct understanding the processes of change in posture of thought that goes against the essence of the capitalist development model currently in force.